Perceptual Improvement of Lexical Tones in Infants: Effects of Tone Language Experience - Tsao, Feng-Ming (Frontiers in Psychology, 2017)
To learn words in a tonal language, tone-language learners should not only develop better abilities for perceiving consonants and vowels, but also for lexical tones. The divergent trend of enhancing sensitivity to native phonetic contrasts and reduced sensitivity to non-native phonetic contrast is theoretically essential to evaluate effects of listening to an ambient language on speech perception development. The loss of sensitivity in discriminating lexical tones among non-tonal language-learning infants was apparent between 6 and 12 months of age, but only few studies examined trends of differentiating native lexical tones in infancy. The sensitivity in discriminating lexical tones among 6–8 and 10–12 month-old Mandarin-learning infants (n = 120) was tested in Experiment 1 using three lexical tone contrasts of Mandarin. Facilitation of linguistic experience was shown in the tonal contrast (Tone 1 vs. 3), but both age groups performed similar in the other two tonal contrasts (Tone 2 vs. 4; Tone 2 vs. 3). In Experiment 2, 6–8 and 10–12 month-old Mandarin-learning infants (n = 90) were tested with tonal contrasts that have pitch contours either similar to or inverse from lexical tones in Mandarin, and perceptual improvement was shown only in a tonal contrast with familiar pitch contours (i.e., Tone 1 vs. 3). In Experiment 3, 6-8 and 10–12 month-old English-learning infants (n = 40) were tested with Tone 1 vs. 3 contrast of Mandarin and showed an improvement in the perception of non-native lexical tones. This study reveals that tone-language learning infants develop more accurate representations of lexical tones around their first birthday, and the results of both tone and non-tone language-learning infants imply that the rate of development depends on listening experience and the acoustical salience of specific tone contrasts.